La musicoterapia y el desarrollo de habilidades sociales en niños con trastorno del espectro autista - Moromisato Higa, Johana Yukari (2021)
Autism Spectrum Disorder (ASD) has as its main characteristics difficulties in the development and generalization of social skills. This work aims to analyze the relationship between music therapy and the development of social skills in children with ASD. For this, an applied review was carried out, conducting a bibliographic search in databases such as EBSCO, APA PsycNET, Proquest and Cogprints, and following the guidelines established by the PRISMA statement (Urrútia and Bonfill, 2013). Finally, 7 articles were selected, of which 5 of these showed significant improvements in various social skills, such as giving a verbal or non-verbal response, imitating, sharing, cooperating, maintaining joint attention, eye contact, reciprocal interaction, and social communication, after applying music therapy interventions to individuals with ASD. While, in the remaining 2 investigations, the improvement did not reach statistical significance. Taking these results into account, it is concluded that music therapy can be an effective style of intervention for the development of social skills in children with ASD, since the use of music can be considered as a tool that promotes social interaction. However, it is necessary to continue studying this style of therapy, to specify which model or type of intervention is more effective for the development of social skills in this population